Association of high mobility group BOX-1 and receptor for advanced glycation endproducts with clinicopathological features of haematological malignancies: a systematic review - Nguyen, Austin H.; Bhavsar, Sheila B.; Riley, Erinn M.; Caponetti, Gabriel C.; Agrawal, Devendra (Contemporary Oncology/Współczesna Onkologia, 2016)
High-mobility group box 1 (HMGB1) is a versatile protein with nuclear and extracellular functions. In the extracellular milieu, HMGB1 binds to several receptors, notably the receptor for advanced glycation end-products (RAGE). The expressions of HMGB1 and RAGE have been described in a variety of cancers. However, the clinical values of HMGB1 and RAGE in haematological malignancies have yet to be evaluated. A systematic search through PubMed and the Web of Science for articles discussing the role of HMGB1 and RAGE in haematological malignancies produced 15 articles. Overexpression of HMGB1 was reported to be associated with malignancy and, in certain studies, poor prognosis and tumour aggressiveness. Only one included study investigated the clinical value of RAGE, in which no significant difference was found between expression of RAGE in CLL neoplastic cells and nonmalignant controls. The discussed associations of HMGB1 and RAGE with clinicopathological characteristics of patients with haematological malignancies warrants further investigation into the prognostic and diagnostic value of both of these molecules.